2019
DOI: 10.1177/0036933019853170
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac crisis mimicking nephrotic syndrome in a post-partum patient

Abstract: Background Coeliac crisis is a life-threatening presentation of coeliac disease. Severe diarrhoea, weight loss, electrolyte imbalances and malnutrition are prominent features. Although mainly a disease of childhood, it can on the rare occasion be diagnosed in adults. Case presentation A 25-year-old female with severe generalised oedema, lower extremity weakness, hypokalemia and profound hypoalbuminemia was referred with an initial diagnosis of nephrotic syndrome. Three months previously she had given birth to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Although relatively uncommon, initial presentation during pregnancy or postpartum period has been described in the literature. [4][5][6][7][8] Most women presenting with CD during pregnancy or the postpartum period had previous signs or symptoms suggestive of CD since childhood that were mild or transient. 5 Common triggers for subclinical CD to manifest include surgery, gluten overloading, smoking cessation, and infection, 7 and the postpartum period should be added to this list.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although relatively uncommon, initial presentation during pregnancy or postpartum period has been described in the literature. [4][5][6][7][8] Most women presenting with CD during pregnancy or the postpartum period had previous signs or symptoms suggestive of CD since childhood that were mild or transient. 5 Common triggers for subclinical CD to manifest include surgery, gluten overloading, smoking cessation, and infection, 7 and the postpartum period should be added to this list.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature identified 48 cases of adults presenting with celiac crisis, 9 but only one case was reported during the postpartum period. 6 Celiac crisis requires urgent hospitalization, fluid resuscitation, correction of electrolyte imbalances, and nutritional support with close monitoring for refeeding syndrome. All cases dramatically improved with a gluten-free diet, and only 1 death was reported (mortality of 2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since completing a GFD, two patients were seriously affected, one with mild biochemical and histological (pathological) benefits, and the other with moderate biochemical and histological (pathological) benefits. Cholesterol tends to play a role in the prevalence of autoimmune disease, which affects between 3.5 percent and 33.3 percent of the population [18][19] . People who demonstrate that CLD or hypertransaminasinemia exists in cases of AILD, patients, other people with AILD, and people who have no clear or apparent reasons for AILD should all be included in the screening process, according to current and previous studies [20][21] .…”
Section: Discussionmentioning
confidence: 99%